1996
DOI: 10.1111/j.1348-0421.1996.tb01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus with X Gene Mutation Is Associated with the Majority of Serologically “Silent” Non‐B, Non‐C Chronic Hepatitis

Abstract: Hepatitis B virus (HBV) with X gene mutations has been a putative pathogen of chronic hepatitis without serological markers of known hepatitis viruses. The aim of this study was to reconfirm whether the HBV with the X gene mutation is associated with these serologically "silent" non-B, non-C (NBNC) chronic hepatitis, alcoholic liver disease (ALD) and autoimmune hepatitis (AIH). HBV DNA was amplified from serum and sequenced in 30 patients with NBNC chronic hepatitis in comparison with 20 patients with ALD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 38 publications
1
38
2
2
Order By: Relevance
“…In a study on hemodialysis patients in Canada, Minuk 12 found occult infection in 3.8% (9239) of the patients; of these, 4 were positive for anti-HBs alone, 1 was positive for total anti-HBc + anti-HBS, and 3 did not present any serological marker. Occult infection is more common in patients with HBV seropositivity 12,29 ; therefore, it is also described in those who are seronegative for HBV 12,30 . The number of patients with occult HBV infection in a given study may be influenced by the sensitivity of the molecular biological technique used, the presence of low viral loads, and the size of the population sample studied 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study on hemodialysis patients in Canada, Minuk 12 found occult infection in 3.8% (9239) of the patients; of these, 4 were positive for anti-HBs alone, 1 was positive for total anti-HBc + anti-HBS, and 3 did not present any serological marker. Occult infection is more common in patients with HBV seropositivity 12,29 ; therefore, it is also described in those who are seronegative for HBV 12,30 . The number of patients with occult HBV infection in a given study may be influenced by the sensitivity of the molecular biological technique used, the presence of low viral loads, and the size of the population sample studied 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Fukuda et al [104] did not find significant differences among the distal and proximal part of X regions in different groups of HBV-infected patients with different clinicopathologic patterns.…”
Section: Mutations In X Genementioning
confidence: 99%
“…On the other hand, previous studies from HBV-endemic areas suggested that prior HBV infection, evidenced by isolated IgG anti-HBc positivity was the most plausible cause of NBNC-NA-NS HCC [9,10]. Although the etiological role of NAFLD in the development of HCC has increased worldwide, this hypothesis has not been tested in HBV-endemic areas where non-B non-C cirrhosis is frequently associated with prior or occult HBV infection and subsequent development of HCC [11,12,13]. Thus, the aim of this study was to investigate the relative etiological role of prior HBV infection and NAFLD in the development of NBNC-NA-NS HCC during the past 10 years in one of the HBV-endemic areas of Korea.…”
Section: Introductionmentioning
confidence: 99%